The Imperial Mind and Biodiversity Conservation: Historical perspective on current debates in biodiversity conservation - Angus Wright (Historia Ambiental Latinoamericana y Caribeña, 2020)
Biodiversity conservation debates have recently been summarized in the phrase, “land-sparing versus land-sharing.” In the land sparing camp are those who seek policies to put as much of the earth’s surface as possible into “protected areas” in which agriculture would be virtually excluded. In order to assure adequate food production, land outside protected areas would be farmed with maximum intensity through techniques that would largely exclude or exterminate wild populations of flora and fauna. In contrast, those who advocate land sharing policies argue for a combination of protected areas alongside agricultural landscapes that would use techniques tending to favor the maintenance of wild populations within a complex matrix of land uses.